Analisis Retorika Politik dalam Debat Publik Kedua Calon Bupati dan Wakil Bupati Kabupaten Ponorogo Tahun 2024 - Muhammad Naufal Aziz; Ayub Dwi Anggoro; Niken Lestarini (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the forms of political rhetoric used by the candidates for regent and vice regent in the second public debate of the 2024 Ponorogo regional elections. The approach used is descriptive qualitative with Aristotle's classical rhetorical analysis techniques, namely ethos, pathos, and logos. Data was obtained from the official transcript of the public debate downloaded from the YouTube channel of the Ponorogo Regency Election Commission. The results of the study indicate that each candidate pair employed different rhetorical strategies: the first pair tended to emphasize ethos and pathos, while the second pair was more dominant in logos and ethos. Political rhetoric is used not only to convey vision and mission but also to subtly attack opponents and build self-image. Thus, this study offers new insights into the role of rhetorical strategies in local political campaigns, which can serve as a reference for aspiring leaders and political consultants in designing more effective campaigns.